Analisis Perbedaan Harga Saham, Volume Perdagangan Saham dan Return Saham Sebelum dan Sesudah Stock Split pada Perusahaan yang Terdaftar di BEI - Negara, Andi Kusuma; Humairoh, Humairoh; Kurniastuti, Cahyani (Universitas Muhammadiyah Tangerang, 2024)
This study aims to determine differences in stock prices, stock trading volume, and stock returns before and after stock splits in companies listed on the IDX for the 2018-2022 period. The research data is daily data for the 2018-2022 period. The population in the study were all companies listed on the IDX that carried out stock splits in the 2018-2022 period. Sampling using a purposive sampling method. Of the 41 companies that did stock splits, 33 companies that met the criteria were sampled. This study used SPSS version 25. The method of analysis in this study used a paired difference test with observations 5 days before and 5 days after the stock split. The results of statistical analysis using the Wilcoxon Signed Rank Test showed that there were significant differences between stock trading volume and stock returns before and after the stock split. Still, there were no significant differences in stock prices before and after the stock split.